Leadership lessons from compelling contexts - Peus, Claudia; Braun, Susanne, Dr; Schyns, Birgit (Monographs in leadership and management ;, 2016)
This volume uses the idiosyncrasies of compelling contexts to teach fundamental leadership lessons that are applicable to other settings. Practitioners and researchers are challenged to deviate from standard models and provided with new ideas for leadership development.